Salvage Surgery for Locoregional Failure in Anal Squamous Cell Carcinoma. Issue 2 (February 2018) - Guerra, Glen R.; Kong, Joseph C.; Bernardi, Maria-Pia; Ramsay, Robert G.; Phillips, Wayne A.; Warrier, Satish K.; Lynch, A. Craig; Ngan, Samuel Y.; Heriot, Alexander G.
Abstract : BACKGROUND: Anal squamous cell carcinoma is a rare cancer with a high cure rate, making research into the treatment of locoregional failure difficult. OBJECTIVE: The purpose of this study was to examine factors related to local treatment failure and determine the outcomes of patients undergoing local salvage resection. DESIGN: This was a retrospective cohort study. SETTING: This study was conducted at a quaternary referral center. PATIENTS: Patients with anal squamous cell carcinoma treated with chemoradiotherapy between January 1983 and December 2015 were included. MAIN OUTCOME MEASURES: The influence of patient-, tumor-, and treatment-related factors on the primary outcome measures of locoregional failure, overall survival, and disease-free survival were investigated. RESULTS: Of 467 patients with anal squamous cell carcinoma, 63 experienced locoregional failure with 41 undergoing salvage resection. Twenty-seven patients (38%) had persistent disease and 36 (62%) developed locoregional recurrence. Multivariate analysis identified tumor stage (HR, 3.16; p < 0.002) as an independent predictor of locoregional failure. Thirty abdominoperineal resections and 11 pelvic exenterations were undertaken with no surgical mortality. At a median follow-up of 20 months (range, 4–150 months), 5-year overall and disease-free survival for the salvage cohort was 51% and 47%. Margin positivity was an independent predictor for relapse post-salvage surgery on multivariate analysis (HR, 20.1; p = 0.027). Nineteen patients (48%) developed further relapse, which included all 10 patients with a positive resection margin, 3 of whom underwent re-resection. Of the 19 patients with relapse, 3 remain alive and 2 have persistent disease. LIMITATIONS: Limitations include the retrospective nature of the database, the prolonged time period of the study, and episodes of incomplete data. CONCLUSIONS: Advanced T stage is an independent predictor of local failure in anal squamous cell carcinoma. Most patients can be salvaged, with a positive resection margin being a strong predictor of further relapse and poor outcome. SeeVideo Abstract athttp://links.lww.com/DCR/A515 .